The Forward looking information disclosure among non-financial firms in Nigeria (2012-2020) (Journal of Economic Research & Business Administration, 2022)
This study investigated the trend of forward looking information disclosure among non-financialfirms in Nigeria over the period of nine years that is, 2012 to 2020. The study employed secondary datawhich were obtained through content analysis of the financial statements of sampled non-financial firms.The population of the study consists of 115 non-financial firms listed on the Nigerian Stock Exchange asat 31st December, 2020. 50 firms were purposively sampled based on the availability of financial statementand listing age over the period examined by the study. The data were analysed using percentagesand charts. The findings of the study revealed that based on the forward looking information disclosureindex employed, Nigerian firms disclosure 35.49 percent forward looking information disclosure levelover the nine year sampled with the year 2019 reflecting the highest level of forward looking informationdisclosure at 39.8 percent. The study concluded that although forward looking information disclosurehad experienced a steady increase in disclosure levels over the sampled period, the level of forwardlooking information is relatively low to satisfy stakeholder needs and therefore recommends that managementof firms in Nigeria should endeavour to improve forward looking information disclosure due toits importance to stakeholder’s decision making.Key words: Forward looking information disclosure, Forward Looking Information Index, VoluntaryDisclosure, Corporate Reporting.